Performance of a vector control for DFIG driven by wind turbine: real time simulation using DS1104 controller board - Sara Mensou; Ahmed Essadki; Issam Minka; Tamou Nasser; Badr Bououlid Idrissi; Lahssan Ben Tarla (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In this research paper we investigate the modelling and control of a doubly fed induction generator (DFIG) driven in rotation by wind turbine, the control objectives is to optimize capture wind, extract the maximum of the power generated to the grid using MPPT algorithm (Maximum Power Point Tracking) and have a specified reactive power generated whatever wind speed variable, the indirect field oriented control IFOC with the PI correctors was used to achieve such as decoupled control. To validate the dynamique performance of our controller the whole system was simulated using dSPACE DS1104 Controller board Real Time Interface (RTI) which runs in Simulink/MATLAB software and ControlDesk 4.2 graphical interfaces.